Analisis Manajemen Risiko Keuangan dan Tenaga Kerja pada UMKM Mie Ayam Mbak Yummi Kota Medan - Ira Sukma Panggabean; Nur Hamidah; Aidil Anwar Ritonga; Putri Kemala Dewi Lubis; Rossy Pratiwy Sihombing (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
MSMEs (Micro, Small, and Medium Enterprises) are one of the important economic pillars in driving local economic growth in various cities in Indonesia. However, MSMEs often face significant challenges, especially related to financial and labor risk management. This study aims to analyze financial and labor risk management at Mbak Yummi Chicken Noodle MSMEs in Medan City. In this study, a descriptive qualitative approach with interviews was used to collect data from business owners and employees. The analysis was conducted with a focus on financial risk management strategies, such as product and service diversification, creative promotion, cash flow management, and access to capital, and labor risk management strategies, including employee cost management, employee development and retention, and effective performance management. The results show that Mbak Yummi Chicken Noodle MSMEs have implemented various strategies to effectively manage financial and labor risks. Product and service diversification, creative promotions, and utilization of online delivery and ordering services help reduce financial risks and maintain revenue stability. Meanwhile, efficient management of employee costs, employee development, and effective performance management help manage labor risks, improve productivity, and maintain service quality. This research shows that effective financial and labor risk management plays an important role in the operational success of Mbak Yummi Chicken Noodle MSMEs.